Foamy macrophages potentially inhibit tuberculous wound healing by inhibiting the TLRs/NF‐κB signalling pathway. Issue 3 (6th April 2022) - Wang, Peng; Yin, Bin; Zhang, Zexin; Mao, Shuting; Bao, Wu; Lian, Wenqin; Fan, Yueying; Hong, Chao; Su, Yingjun; Jia, Chiyu
Abstract: To characterise the distribution, classification, and quantity of foamy macrophages (FMs) in tuberculous wound tissue and the relationship between FM and delayed healing of tuberculous wounds. Morphological studies were performed to explore the distribution of FM and Mycobacterium tuberculosis (Mtb) in tuberculous wounds, with acute and chronic wounds included for comparison. Phorbol‐12‐myristate‐13‐acetate stimulation‐differentiated THP‐1 cells were treated with Mtb to induce their differentiation into FM with oxidised low‐density lipoprotein treatment serving as a control. Relative cytokine levels were determined by quantitative PCR and Western blotting. Varied co‐culture combinations of Mtb, THP‐1, FM, and fibroblasts were performed, and proliferation, migration, ability to contract collagen gel, and protein levels of the chemokines in the supernatants of the fibroblasts were assessed. The differentially expressed genes in human skin fibroblasts (HSFs) after co‐culture with or without FM were identified using microarray. Many FM were found in the tissues of tuberculous wounds. The FM that did not engulf Mtb (NM‐FM) were mainly distributed in tissues surrounding tuberculous wounds, whereas the FM that engulfed Mtb (M‐FM) were dominantly located within granulomatous tissues. Co‐culture experiments showed that, with the Mtb co‐culture, the portions of NM‐FM in the total FM grew over time. The migration, proliferation, chemokine secretion, and the ability of fibroblasts to contract collagen gel were inhibited when co‐cultured with Mtb, FM, or a combination of the two. Further investigation showed that the TLRs/NF‐κB signalling pathway is involved in fibroblast function under the stimulation of FM. TLRs and NF‐κB agonists could reverse the phenotypic changes in HSFs after co‐culture with FM. The tuberculous wound microenvironment composed of Mtb and FM may affect wound healing by inhibiting the functions of fibroblasts. FM potentially inhibit fibroblasts' function by inhibiting the TLRs/NF‐κB signalling pathway in tuberculous wounds.